A higher response of plasma neuropeptide Y, growth hormone, leptin levels and extracellular glycerol levels in subcutaneous abdominal adipose tissue to Acipimox during exercise in patients with bulimia nervosa: single-blind, randomized, microdialysis study - Smitka, Kvido; Papezova, Hana; Vondra, Karel; Hill, Martin; Hainer, Vojtech; Nedvidkova, Jara (Nutrition & metabolism, 2011)
BACKGROUND: Neuropeptide Y (NPY) is an important central orexigenic hormone predominantly produced by the hypothalamus, and recently found to be secreted in adipose tissue (AT). Acipimox (Aci) inhibits lipolysis in AT and reduces plasma glycerol and free fatty acid (FFA) levels. Exercise and Aci are enhancers of growth hormone (GH) and NPY secretion and exercise may alter leptin levels. We expect to find abnormal neuropeptidergic response in plasma and AT in patients with bulimia nervosa (BN). We hypothesize that Aci influences these peptides via a FFA-independent mechanism and that Aci inhibits lipolysis through a cyclic adenosine monophosphate (cAMP)-dependent pathway. Dysregulations of the AT-brain axis peptides might be involved in binge eating as is the case in BN. METHODS: The objective of this study was to determine the responses of plasma NPY, GH, leptin, FFA and glycerol levels to exercise in BN patients and healthy women (C) given the anti-lipolytic drug Aci or placebo. The secondary objective of this study was to compare the responses of extracellular glycerol levels and plasma glycerol levels to exercise alone or together with Aci administration in BN patients and C women. Extracellular glycerol was measured in vivo in subcutaneous (sc) abdominal AT using microdialysis. Eight BN and eight C women were recruited for this single-blind, randomized study. Aci or placebo was given 1 hour before the exercise (45 min, 2 W/kg of lean body mass [LBM]). NPY, GH, leptin, FFA, glycerol plasma and AT glycerol levels were measured using commercial kits. RESULTS: The primary outcome of this study was that the exercise with Aci administration resulted in plasma NPY and GH increase (after a 45-minute exercise) and leptin (after a 90-minute post-exercise recovering phase) increased more in BN patients. The secondary outcomes of this study were that the exercise with Aci administration induced a higher decrease of extracellular glycerol in BN patients compared to the C group, while the exercise induced a higher increase of glycerol concentrations in sc abdominal AT of BN patients. Plasma glycerol levels decreased more in BN patients and plasma FFA levels were depressed in both groups after the exercise with Aci administration. The exercise induced similar increases in plasma NPY, GH, FFA and glycerol levels, and a similar decrease in the plasma leptin level in both groups. CONCLUSIONS: We confirm the results of a single-blind, randomized, microdialysis study, i.e. that the Aci-induced elevation in plasma NPY and GH levels during the exercise is higher in BN patients and that Aci increased plasma leptin levels in the post-exercise recovering phase (90-minute) more in BN patients. The post-exercise rise (45-minute) in AT glycerol is much more attenuated by acute Aci treatment in BN patients. Simultaneously, we found facilitated turnover of plasma glycerol after the exercise together with Aci administration in BN. Our results support the hypotheses that Aci exerts an effect on the FFA-independent and cAMP-dependent mechanism. TRIAL REGISTRATION: Australia and New Zealand Clinical Trials Register (ANZCTR): ACTRN12611000955910.